2015
DOI: 10.1517/17425247.2015.1031216
|View full text |Cite
|
Sign up to set email alerts
|

Topically applied methotrexate is rapidly delivered into skin by fractional laser ablation

Abstract: MTX absorbs rapidly into mid-dermis of AFXL-processed skin with minimal transdermal permeation until skin saturation, suggesting a possible alternative to systemic MTX for some skin disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 38 publications
3
38
0
1
Order By: Relevance
“…This study demonstrates that after skin saturation, MTX has been delivered into the immediate vicinity of the MAZs through coagulation zones ranging from median 6 to 47 μm. However, a previous in vitro study on AFXL‐assisted MTX delivery demonstrated that within the first hours of diffusion, radial biodistribution was delayed but not hindered, by coagulation zones of median 47 μm . Overall, these findings suggest that AFXL is suitable for topical MTX delivery since MTX diffuses through various thicknesses of thermal coagulation, while the initial rate of absorption may be influenced by the generated coagulation zones.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This study demonstrates that after skin saturation, MTX has been delivered into the immediate vicinity of the MAZs through coagulation zones ranging from median 6 to 47 μm. However, a previous in vitro study on AFXL‐assisted MTX delivery demonstrated that within the first hours of diffusion, radial biodistribution was delayed but not hindered, by coagulation zones of median 47 μm . Overall, these findings suggest that AFXL is suitable for topical MTX delivery since MTX diffuses through various thicknesses of thermal coagulation, while the initial rate of absorption may be influenced by the generated coagulation zones.…”
Section: Discussionmentioning
confidence: 71%
“…Receiver compartment of this intervention has been utilized as control sample in a previous study .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to number of open channels, also channel depth may have an impact on the resultant FI, because superficial channels potentially possess less capability than deep channels to enhance drug uptake. The impact of channel depth on drug uptake was specifically demonstrated in a previous study using topically applied methotrexate (MTX), a small, hydrophilic drug (MW 454, log P = −1.8), and deeper AFXL channels resulted in better uptake of MTX than more superficial channels. In accordance, our results may be representative for small, hydrophilic drugs applied in a clinical setting, as well as OCT may serve as a useful technique to determine the time frame to enhance drug delivery using other laser settings.…”
Section: Discussionmentioning
confidence: 96%
“…In support of this notion, previous FC‐studies have observed a depth dependent uptake for hydrophilic compounds e.g., methotrexate, (log P = −1.85) and slightly lipophilic compounds e.g., prednisone (log P = 1.46) and diclofenac (log P = 1.90) but not for hydrophobic drugs, such as lidocaine (log P = 2.44), ingenol mebutate (log P = 2.51), and imiquimod (log P = 2.7) .…”
Section: Discussionmentioning
confidence: 66%
“…Data represents median values with corresponding interquartile range. ingenol mebutate (log P ¼ 2.51), and imiquimod (log P ¼ 2.7) [9,11,16,17,[27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%